O bom e o mau aluno: representações sociais de professores de ensino fundamental sobre sucesso e sobre fracasso escolar - Zangrande, Helen Junara Balbinotti (2021)
The theme of the alleged failure and success at school is recurrent in the Brazilian educational context. This research was done at the Municipal Education Network, in Dois Vizinhos, Paraná, where Psychology and Psychopedagogy professionals who perform evaluations claim that there is pattern of complaints in referrals they receive. In general, this pattern points to learning difficulties, school lag, development delay and children’s behavioral problems, based on what is generically called school failure.The objective of this research was to analyze the forms which teachers of the Elementary School I, of this municipal network, socially represent failure and success at school. The participants of this search were 27 teachers of both sexes, with at least 5 years of experience. For data gathering, 3 procedures were performed: free word evocation technique; substitution technique, aiming to capture the silent zone of social representations; and semi-structured interviews. The data obtained by the 2 first procedures were treated according to the orientation for identifying the core of social representation. The data obtained by the interview were conducted using Content Analysis. The results indicate that the central element of the social representations about failure at school, to the researchers, revolves around the Family, the teacher and the educational system as a whole. Teachers believe that there is a strong association between the parents’ non-participation in the kids’ school lives and the failure at school. Though, as for the teacher, certain connections were pointed out between the lack of preparation and commitment, the methodology and demotivation with the students’ failing. In the silent zone of these representations the students’ emotional factors were considered to influence school failure; results that are different from those obtained by the other techniques used in the research, which the attitudes and behavior of the student were considered more important. Regarding the representation of school success, it was observed that the student, family and teacher are perceived as the most responsible. At those conditions, it was observed that if the family met the given expectations, it became co-responsible for building school success. As for the role of the teacher, proved to be by his/her pedagogical method, which the teacher appears as the manager of the process of obtaining success. Therefore, in the representations of the surveyed teachers, they are more responsible for the success than for the failure of the student. As for the students, according to the participants, the contribution to the success has to do with the acts and behavior that would facilitate the development, socialization and appropriation of the knowledge. The results depict that the representation acquired by the normative methods were not significantly different from those observed when harvested in the mute area. Finally, we state that the social representations analyzed in this research reflect not phenomena per se, but ideas that result from forms and norms created in and by school culture; and the educational systems that set standards that are impossible to achieve, because in fact there is no place for everyone in the world as it is currently organized; but also by those who unconsciously underpin them.